2018
DOI: 10.2337/db18-992-p
|View full text |Cite
|
Sign up to set email alerts
|

Late and Missed Meal Boluses with Multiple Daily Insulin Injections

Abstract: Background: Using sensor augmented pump data, late or missed meal boluses have shown a strong correlation with higher A1c levels, particularly in adolescents. With the Type Zero InControl Phone connected to a Dexcom G5 sensor and Novo insulin pens with memory and connectivity it is now possible to evaluate for late and missed meal boluses in MDI users. Methods: For this study 326 days of CGM data were evaluated from 24 subjects (mean age 33, range 15-59 years). Seven days of data were analyzed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…7,39 A recent study observed that the rate of late or missed bolus injections was 27% in people using MDI therapy, and that missed bolus injections correlated with higher HbA 1c levels. 40 In a study of youths receiving insulin pump therapy, two missed bolus injections each week was associated with an increase in HbA 1c of 0.5% (5 mmol/mol). 39 Our findings indicate that a connected pen may help people to reduce the number of missed bolus injections and to properly adjust doses, thus leading to better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…7,39 A recent study observed that the rate of late or missed bolus injections was 27% in people using MDI therapy, and that missed bolus injections correlated with higher HbA 1c levels. 40 In a study of youths receiving insulin pump therapy, two missed bolus injections each week was associated with an increase in HbA 1c of 0.5% (5 mmol/mol). 39 Our findings indicate that a connected pen may help people to reduce the number of missed bolus injections and to properly adjust doses, thus leading to better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects used the Type Zero InControl Phone connected to a Dexcom G5 sensor and Novo insulin pen with memory. 28 Seven days of data were analyzed initially and 1 month later. More than one-quarter (27%; range = 8-55%) of subjects either took a late meal-time injection (13%, range = 2-30%) or missed a meal-time injection (14%, range = 2-38%).…”
Section: Missed or Delayed Insulin Dosesmentioning
confidence: 99%
“…16 It is now estimated that mealtime insulin dosing is late or missed with 25%-27% of meals. 17,18 Modeling studies suggest that insulin omission can lead to worse glycemic control. For example, omitting 2.1 meal-related injections per week can lead to an increase in HbA 1c of at least 0.3%-0.4%, omitting 2.1 bolus injections per week would lead to an increase in HbA 1c of 0.2%-0.3%, and omitting 39% of all injections would lead to an increase in HbA 1c of 1.8%.…”
Section: Consequences Of Poor Pharmacoadherence To Insulin Therapymentioning
confidence: 99%